USE OF LINGUISTIC SCIENCE APPROACH DURING ORGANIZATION OF EXTRACURRICULAR WORK ON FOREIGN LANGUAGE ACCREDITATION LEVEL IN EDUCATIONAL INSTITUTIONS AS A CONDITION FOR ENSURING STUDENTS 'EMOTIONAL EMOTIONALITY (Pedagogy of Higher and Secondary Education, 2011)
This article considers the features of use (the country study approach during the organisation out-of-class work in a foreign language as maintence conditions of training emotionality of students.
Keywords: country study approach; out-of-class work in a foreign language; training emotionaly